2021
DOI: 10.3390/bs11050064
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic and Typhoon: Positive Impacts of a Double Disaster on Mental Health of Female Students in the Philippines

Abstract: Humanitarian emergencies pose a great challenge to how all sectors perform their functions in society. In several countries, these emergencies combined the pandemic and other man-made and natural disasters: “double disaster”, which affected the health, safety, and well-being of both individuals and communities. Students are a particularly vulnerable population for mental health problems considering the challenges with their transitions to adulthood. Using narrative analysis, this study explored the impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…They feel sick whenever they had many activities to do, have slow internet, and are without someone to ask (Rotas & Cahapay, 2020). Cueto and Agaton (2021) noted that stress and anxiety are the expected health effects whenever students suffer difficulties. In addition to the adverse health effects of disrupted sleep cycles, increasing internet use can influence students' physical and mental health.…”
Section: Health-related Problemsmentioning
confidence: 99%
“…They feel sick whenever they had many activities to do, have slow internet, and are without someone to ask (Rotas & Cahapay, 2020). Cueto and Agaton (2021) noted that stress and anxiety are the expected health effects whenever students suffer difficulties. In addition to the adverse health effects of disrupted sleep cycles, increasing internet use can influence students' physical and mental health.…”
Section: Health-related Problemsmentioning
confidence: 99%
“…Accordingly, there is some potential for solving the problem in the cooperation of teachers and students. Heavy and extremely time-consuming activities can be replaced by more interesting and enjoyable ones [74]. At the same time, the potential is created for the re-organization of educational content with the help of modern technological capabilities [75; 76], taking into account the existing support in the student environment, which can be implemented in teamwork [78], [79] that is the direction for further research.…”
Section: Discussionmentioning
confidence: 99%
“…When the demographic variables are considered, Cueto and Agaton (2021) revealed in their study that the female students find more strength in their faith, which is why they possess higher spiritual well-being compared to men (Coppola et al, 2021;Yahaya et al, 2012). Ahmadphoori and Motaghi (2020) concluded that spiritual health is an important aspect in female adolescents, and the role of the family in adolescents' mental health is considered crucial too.…”
Section: June Recoletos Multidisciplinar Y Research Journalmentioning
confidence: 99%